Mid-Level Health Providers- their perceptions and background knowledge pertaining to Comprehensive Primary Health Care and Health and Wellness Center - Hitesh Shah; Priti Solanky; Rachana Kapadia; Sunil Nayak (Indian Association of Preventive and Social Medicine, 2020)
Introduction: To achieve universal health coverage, concept of Health and Wellness Center (HWC) was given under Ayushman Bharat. For providing health care services through HWC, cadre of Mid-Level Health Provider (MLHP) is introduced who would be leading primary health care team at HWC. Objective: This study was undertaken with objective to assess the factors favoring to join this course and baseline knowledge of Comprehensive Primary Health Care (CPHC) and Health and Wellness Center (HWC) among course candidates Method: It was a cross sectional study conducted among candidates of certificate course in community health at PSC (Program Study Center) of Medical College at South Gujarat through self-administered semi-structured Performa. Results:Career changing opportunity was considered as a major factor to pursue CCCH course and obtaining MLHP position at HWC. Accessibility of HWC and role in advocacy generation were perceived major needs for it in community. Preventive, Promotive and Curative functions were mentioned as functions of HWC and geographical accessibility with delivery of functions in effective manner were perceived as chief characters of ideal HWC. Along with these, they mentioned cleanliness of center, community involvement and client satisfaction as its other characters. Conclusion and Recommendations:Baseline knowledge of the candidates pertaining to need, functions and ideal HWC was found almost satisfactory but it needed reinforcement and clarity. These results should be used for proper planning of curriculum and implementation of CCCH course to fulfill gaps in knowledge. We recommend that similar exercise should be carried out at all PSCs for effective implementation of course curriculum.